Istilah undang-undang : English-Malay, Malay-English, Arabic-English - Thomson Reuters Legal (Petaling Jaya, Selangor : Sweet Maxwell/Thomson Reuters, 2016)
English-Malay, Malay-English, and Arabic-English dictionary of legal terms.
Previous edition was published 2008, edited by Jaques, Rachel.
English, Malay and Arabic.
Keywords: Law -- Dictionaries; English language -- Dictionaries -- Malay; Law -- Dictionaries -- Malay; Malay language -- Dictionaries -- English; Law -- Dictionaries -- Arabic; Arabic language -- Dictionaries -- English